Promotion of Para athlete well-being in South Africa (the PROPEL studies): Profiles and prevalence of psychological distress - Badenhorst, M.; Runciman, P.; Brown, J. C.; Swartz, L.; Derman, W. E. (Journal of Science and Medicine in Sport, 2021)
Objectives: There is a paucity of research investigating mental health in Para athletes. The aim of this study was to describe mental health concerns of a representative sample of South African Para athletes. Design: A descriptive, cross-sectional survey was conducted at the 2019 National Championships for athletes with impairments. Methods: Mental health was measured with the Trait component of the State/Trait Anxiety Inventory (STAI-T), and the Kessler Psychological Distress Scale (K-10). Between-group differences were analysed using the Mann-Whitney U test or one-way ANOVA. Results: A total of 125 athletes were included. The average score for the STAI-T was 39 (±9) units, whilst a quarter (25%) of all athletes scored =45. The mean K-10 questionnaire score was 20 (±6) units. K-10 scores indicated that 12 % of athletes may meet formal definitions for anxiety and/or depressive disorders (score of =28), while 76 % of athletes have a high level of subclinical symptoms (score of =16). On average, females (36±9) had better STAI-T scores than males (40±9; p=0.02) and married athletes (33±9) had better scores than unmarried athletes (40±9; p=0.002). K-10 scores were also significantly better in married than in unmarried athletes (p=0.002), but there was no difference between sexes. Neither the K-10 nor STAI-T was associated with level of competition, sport code or impairment type. Conclusions: The study identified a high prevalence of psychological distress and anxiety among South African Para athletes, compared to the general population. There is a need to further understand factors contributing to mental health in this population.